2012
DOI: 10.1614/wt-d-11-00184.1
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-Resistant Giant Ragweed (Ambrosia trifida) Control in Dicamba-Tolerant Soybean

Abstract: Glyphosate-resistant (GR) giant ragweed has been confirmed in Ontario, Canada. Giant ragweed is an extremely competitive weed and lack of control in soybean will lead to significant yield losses. Seed companies have developed new herbicide-resistant (HR) crop cultivars and hybrids that stack multiple HR traits. The objective of this research was to evaluate the efficacy of glyphosate and glyphosate plus dicamba tank mixes for the control of GR giant ragweed under Ontario environmental conditions in dicamba-tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 23 publications
2
58
0
2
Order By: Relevance
“…Furthermore, reference [17] reported moderate, yet variable, control of giant ragweed ranging from 33% to 80% from mesotrione plus atrazine. In dicamba-tolerant soybean, up to 100% control of GR giant ragweed 8 WAA has been reported from dicamba PP application [19]. On the contrary, reference [20] reported poor control (30%) of GR giant ragweed with dicamba applied PP in dicamba-tolerant soybeans, however, control increased to over 80% when accompanied by a dicamba POST application.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
“…Furthermore, reference [17] reported moderate, yet variable, control of giant ragweed ranging from 33% to 80% from mesotrione plus atrazine. In dicamba-tolerant soybean, up to 100% control of GR giant ragweed 8 WAA has been reported from dicamba PP application [19]. On the contrary, reference [20] reported poor control (30%) of GR giant ragweed with dicamba applied PP in dicamba-tolerant soybeans, however, control increased to over 80% when accompanied by a dicamba POST application.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
“…This is due to the fact that giant ragweed is very sensitive to growth hormone herbicides [28] [29]. For example, a study in Ontario, Canada reported 99% control of glyphosate-resistant giant ragweed with dicamba applied in a burndown treatment before planting soybean [30]. Giant ragweed control with saflufenacil plus imazethapyr was 89% at 21 DABT; however, control was reduced to 63% at soybean harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean cultivars with traits conferring resistance to pre-plant or POST applications of 2,4-D or dicamba are being developed and may be commercialized in the near future [30] [31]. This may provide more flexibility of POST 2,4-D or dicamba application for control of glyphosate-resistant weeds, including giant ragweed [30] [32].…”
Section: Resultsmentioning
confidence: 99%
“…Glyphosate 처리시기를 콩 파종 후 4-6주까지 지연하여 처리하면 작 물과의 경합에 의해 잡초발생이 억제되기 때문에 glyphosate 의 잔효성 부족을 보상할 수 있으며, glyphosate 저항성 콩 에서 잡초방제의 30% 효과는 작물경합에 기인한다 (Shaner, 2000). Dicamba 저항성 콩에서 glyphosate + dicamba를 토양처 리한 후 glyphosate + dicamba 제초제를 1회 처리한 체계 처리는 glyphosate 저항성잡초인 돼지풀류(Ambrosia trifida) 방제에 매우 효과적이다 (Vink et al, 2012 Imidazolinone 저항성 벼에서 사용되는 제초제인 imazethapyr는 토양 및 경엽처리에서 넓은 살초효과가 있 는 ALS 저해형 제초제이다 (Croughan, 1994). Imazethapyr 저항성 벼에서 발생하는 잡초성 벼, 피, Althernanthera philoxeroides는 quinclorac 혹은 penoxsulam과 imazethapyr 혼합제 처리 후, imazethapyr 혹은 imazamox 경엽처리와 같은 체계처리에 의하여 방제되었다 (Webster et al, 2012).…”
Section: 제초제 저항성작물 경작지에서 발생하는 잡초unclassified